An Efficient Multi-dimensional Data Aggregation Scheme for Fog-Assisted Wireless Body Area Network. Issue 1 (1st June 2022) - Fan, Hongbin; Luo, Yiheng
Abstract: The rapid development of wireless body area network and monitoring technology has brought new opportunities for the later rehabilitation of patients. Due to the limited computing power and power of wireless body area network (WBAN) sensor nodes, combining WBAN with fog computing is one of the feasible solutions for remote monitoring. Wireless body area network can exchange medical information in real time, which is an effective way to improve medical services. The WBAN is inefficient and vulnerable to attacks, leading to leakage of user privacy information. This paper proposes an efficient data aggregation scheme for fog-assisted WBAN. The analysis shows that the scheme can resist the existing attack. The security analysis shows that the scheme meets the privacy and security requirements of data aggregation in WBAN. Compared with existing schemes, this scheme has an efficiency advantage.